2012
DOI: 10.1088/0022-3727/45/30/305101
|View full text |Cite
|
Sign up to set email alerts
|

The fixed oxide trap modelling during isothermal and isochronal annealing of irradiated RADFETs

Abstract: The density of fixed traps (FTs), ΔN ft (cm−2), during isothermal annealing of irradiated radiation-sensitive field-effect transistors (RADFETs) from room temperature to 200 °C has been modelled. The modelling has shown that a simple, two-defect model (2DM), containing two defect types: one defect type for positively charged FTs (PCFTs), and another for negatively charged FTs (NCFTs), is applicable for the temperatures up to 100 °C. However, the three-defect model (3DM), which includes additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…To fit the ΔV ft , i.e. ΔV T , during SA, we will use the model for the annealing of radiation-induced defects developed in reference [7], which is confirmed in other experiments [8,10]. Using Equations ( 8)- (10) from reference [7] and reactions (7) and (8), the dependence of densities of E 𝛾 , N E 𝛾 (t ), and of E s , N E s (t ), respectively, on time during SA, can be obtained as follows: where N E 𝛾 (0) and N E s (0) are the densities of E γ and E s after irradiation, i.e.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…To fit the ΔV ft , i.e. ΔV T , during SA, we will use the model for the annealing of radiation-induced defects developed in reference [7], which is confirmed in other experiments [8,10]. Using Equations ( 8)- (10) from reference [7] and reactions (7) and (8), the dependence of densities of E 𝛾 , N E 𝛾 (t ), and of E s , N E s (t ), respectively, on time during SA, can be obtained as follows: where N E 𝛾 (0) and N E s (0) are the densities of E γ and E s after irradiation, i.e.…”
Section: Resultsmentioning
confidence: 82%
“…Also, the values of fading for V G,i = 5 V are similar for both oxide thicknesses. Here it should be noted that the case without an external voltage on the gate (V G,i,a = 0) of Al-gate pMOSFETs corresponds to a small internal positive voltage on the gate of V wf = 0.33 V due to the difference in a work function between the Al-gate and n-type silicon substrate, resulting in small external positive electric field in the gate oxide [8].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining two gate biases show the same behavior (not shown). It can be concluded that the annealing of fixed traps determines fading (Ristić et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…20 Since the total dose sensitivity of an MOS transistor increases with the gate oxide thickness, 21 MOS dosimeters are built with thick gate oxides. [22][23][24][25] However, to fabricate them sufficiently thick, ad hoc processes are needed leading to an increased manufacturing cost. To be able to produce these dosimeters in standard complementary metal-oxide-semiconductor (CMOS) processes with high dose sensitivity, the FOX field effect transistor (FOXFET) dosimeter has recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…MOS dosimeters are MOS transistors in which the accumulative threshold voltage shift (normalΔVT$\Delta V_T$) is used to quantify the absorbed dose 20 . Since the total dose sensitivity of an MOS transistor increases with the gate oxide thickness, 21 MOS dosimeters are built with thick gate oxides 22–25 . However, to fabricate them sufficiently thick, ad hoc processes are needed leading to an increased manufacturing cost.…”
Section: Introductionmentioning
confidence: 99%